Marginal hazard distribution in network structures - Juozas Augutis; Ričardas Krikštolaitis; Elvyra Augutienė (Lietuvos Matematikos Rinkinys)
The subject of this work is the analysis of hazard distribution in the network systems. In the age when transport flows in the railway and road systems, information flows in the internet channels, etc. intensify, hazard distribution in the network systems becomes a more relevant and important issue.  In the paper various theoretical hazard type distributions in the network systems are analysed. Mathematical model of hazard distribution and accumulation in the nodes of the network was created.